MUSIK ROK SEBAGAI BENTUK KONSTRUKSI SOSIAL DALAM MEREFLEKSIKAN PERUBAHAN SOSIAL GENERASI MUDA - Alialamsyah Kusumadinata (Jurnal Sosial Humaniora, 2012)
The main objective of this study was to determine the extent of rock music in the form of social construction reflecting social changes young people. The research method used a case study with a qualitative approach. The data were collected through participant observation, in-depth interviews, and a literature review. Determination of informants was done by snow balling (snowball) on the basis of the criteria on the younger generation who liked and interested in rock music. While the researchers observed in active for about a year (2010-2011). The results showed that the level of penetration of significant symbols in rock music at the secondary socialization process of the four informants produce diverse identities. Produce the identity of the informant first "gray", while the second and third of the informants produce identity "critical". Meanwhile, of the four informants significant penetration of the symbols of identity that produces rock music "apolitical". While social conditions will be transformed into a new social movement where a sharp increase of the flow of imports to new ideas, goods and values of the foreign community as opposed to the values of the local community. The social construction that is represented by one of rock music from the band "Tengkorak Band" confirms the importance of the individual has a critical awareness of the uniqueness of the local cultural values as the primary goal of development. Therefore, the social construction of the public, especially young people better understand the local culture terminology archipelago (Indonesian Cultures).